Design and Application of the Blended Teaching Mode in the Curriculum of Pharmacokinetics - Liu, Zhongbing; Wang, Shuzao; Lin, Yan; Zhou, Meiling; Jing, Pei; Zhong, Zhirong (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Pharmacokinetics is one of the main courses of pharmacy majors in medical colleges and universities. The course is highly practical involving multidisciplinary collaboration, with strong logical reasoning and complex calculations. But the widespread traditional teaching methods resulted in poor practical application ability, self-learning ability, and problem-solving ability of students. Objectives: To enhance the students' knowledge and problem-solving ability, we focused on the curriculum reform of pharmacokinetics. Materials and Methods: It was based on the online and offline mixed teaching mode including revising the training program and syllabus, reconstructing the teaching staff, constructing online courses, designing class teaching, and careful teaching implementation, and construction of evaluation system. Finally, questionnaire survey was conducted to evaluate the implementation effect about the "online + offline" hybrid teaching mode. Results: It showed that the mixed online and offline teaching mode can help to solve the problem of difficulty in both teaching and learning the pharmacodynamics course. It changed the students' rigid learning methods that are not conducive to the cultivation of applied high-quality pharmaceutical talents. Moreover, this teaching reform enhanced the students' problem-solving ability. It achieved the course goals of cultivating students to be competent in medication guidance, drug quality control, and supervision positions, and to have the basic ideas and abilities to innovatively research and solve drug quality problems. Conclusion: This blended teaching mode may be an effective alternative to conventional approaches in pharmaceutical education.
Keywords: Curriculum; Blended teaching mode; Pharmacokinetics; Pharmaceutical students